PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP BUDAYA ORGANISASI - Herminingsih, Anik (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2011)
Bank Mandiri is the biggest state-owned bank in the total asset that were previously performing poorly. One of management strategies to improve performance is by the implementation of organizational culture. Organizational culture is very important in supporting the performance of bank as financial services companies. Implementation of a comprehensive new work culture conducted in 2005 and the process is still running until today. The study aims to examine the influence of transformational leadership on organizational culture. The research sample are 113 credit managers at Bank Mandiri Region VII (Central Java and Yogyakarta), and the data was analysed using regression equations. The results showed that transformational leadership has positive and significant impact on organizational culture. Inspirational motivation dimensions of transformational leadership has a positive and significant inflences on the culture dimensions of involvement, adaptability, and mission. Individual consideration dimension of transformational leadersip has a positive and significant inflences on the cultural dimensions of consistency.